The capacity of absorption and the management of human resources in asymmetrical strategic alliances: the case of Moroccan SMEs - El Hammoumi, Ahmed; Seghyar, Nabil; El Hammoumi, Mohammed; El-Ouali, Adil (Business, Management and Economics Engineering, 2025)
Purpose – The aim of this work is to analyze human resources mechanisms in order to enhance the absorption capacity of SME in strategic alliances with foreign partners, the goal being to favor the transfer of know-how to these enterprises. Research methodology – The methodology applied is quantitative, based on a questionnaire addressed to 108 SME. SPSS 25 software was used to analyze the result. Findings – The results of the study underline the critical role employees’ play in the knowledge transfer process by dwelling on the need of an absorption and assimilation capacity since businesses with such capacities are conducive to the acquisition, putting into use and development as well as the creation of new skills and know-how. Research limitations – The quantitative approach of this research could be complemented by qualitative analysis. Additionally, generalizing the results from a sample of SMEs opens avenues for future research in other developing countries. Temporal and contextual extension could also enhance the relevance of the conclusions. Practical implications – Our results could be used to provide key indicators for managers of SMEs engaged in strategic alliances. The guidelines aim to streamline the transfer, acquisition, and development of new skills and know-how from foreign partners. Originality/Value – This study innovatively clarifies the administration of human resources in SMEs’ in asymmetrical strategic alliances, offering valuable insights for research into management practices.